Pengaruh Penggunaan Canva terhadap Kreativitas dan Minat Belajar Siswa pada Mata Pelajaran Teknologi Informasi dan Komunikasi - Muhamammad Fadili; Sucipto Sucipto; Sri Yuni Hanifah (Universitas Negeri Makassar, 2026)
Development digital technology has bring change significant in the world of education , especially in the learning process in the 21st century . Technology integration in learning No only functioning as tool help , but also as means strategic For increase motivation and results Study participant education. Research This aim For know influence use of learning media based Canva application against creativity and interest Study students in the eye lesson Technology Information and Communication in schools medium vocational Robatal Sampang. Research use approach quantitative with quasi-experimental design method type Nonequivalent Control Group Design. Research Sample is student X-RPL class as group experiment (23 students) and X-TKR as group control (18 students ). Instrument study in the form of questionnaire creativity and interest learning that has been tested validity and reliability. Data were analyzed through normality, homogeneity, and t-test tests using SPSS. The results of the study show that there is difference significant between group experiments and controls , where students learn use Canva app has level creativity and interest Study more tall compared to with students who study use method conventional . Use Canva app is proven effective in increase participation active, understanding materials, as well as motivation student in learning Technology Information and Communication. Research Conclusion This is that learning media Canva- based influential positive to creativity and interest Study vocational school students. Implications from results study This encourage teachers to utilizing interactive digital media in create more learning innovative, attractive, and appropriate with need digital generation .